Sustainability Reporting Alignment: A Systematic Review of King V Code, IFRS S1/S2, Assurance and Combined-Assurance Maturity in South Africa - Okere, Wisdom; Ambe, Cosmas (International Review of Management and Marketing, 2026)
This study interrogates the evolving alignment between South Africa’s corporate governance architecture (King V) and emergent global sustainability disclosure regimes. This systematic review assesses the alignment of the transition from King IV (apply or explain model) to King V (Outcome-based, assurance-driven policy) with the requirements of IFRS S1/S2. A PRISMA methodology, with guided search and screening (2017-2025), focused on South Africa and data were extracted from 27 peer-reviewed articles covering context, theory, linkages to IFRS S1/S2, assurance/combined assurance, key findings and gaps. The research findings reveal that King IV establishes a solid foundation for ethical leadership, board accountability and integrated thinking. (i) Board reforms under King IV improved governance and the remuneration framework, (ii) King IV is integrated in South Africa’s corporate practice and common law (a critical driver for King V’s outcomes-orientation and IFRS S1/S2 integration. (iii) AI/ digital technology governance frameworks but underutilised. This synthesis demonstrates that King V is a governance structural reform, highlighting the shift towards digital governance and improved assurance. The study proposes a structured, board-level roadmap that includes governance of sustainability data, ISSB controls, climate risk integration, combined-assurance mapping, assurance scoping, board committee oversight, and transparent reporting, with sector-specific guidelines for extractive, banking and consumer sectors.